THE CORRELATION BETWEEN SPEAKING ENGLISHANXIETY AT THE EIGHT GRADE STUDENTS’ SPEAKINGSKILL AT SMPN 108 JAKARTA IN ACADEMIC YEARS 2018 - Elinda Andita Putri; Arjulayana - Arjulayana (Globish: An English-Indonesian Journal for English, Education, and Culture, 2019)
Speaking is a complex skill to be developed by students because of factors such as pronunciation, lack vocabulary, grammar structure, or just simply because some students are not motivated to learn it.  This study aim to discuss about students 'anxiety and students' speaking skills. The object of research in this study was the eighth graders at SMPN 108  Jakarta. This study uses a quantitative approach in the correlation model.Instruments or tools used by researcher to collect data and divided into two types. First, a questionnaire (questionnaire) which contains 16 statements with 5 rating scales, which are used to measure the level of anxiety of students in the process of learning English. The second speaking test instrument of speaking skill. In analyzing the data, in analysis the data researcher used Pearson Product Moment Correlation to find out the correlation of data result completed by SPSS program. In the results of this research analysis have been shown that student anxiety in their speaking test that is  0.306, this value shows a positive correlation between the two variables. This result is seen from the table the estimated correlation of 0.306 is between 0.200-0.399, means the correlation strength of the two variables is low correlation. Though, r value showed low correlation interpretation, but the result explained us that the language anxiety has positive influence on students speaking skill to students SMPN 108. In conclusion  the result of this research can be concluded that there is significant correlation, this shows that students’ English anxiety has an effect on the students’ speaking skill.Keyword: Correlation, Students’ Anxiety, Students’ Speaking Skill.